Penggunaan Gaya Bahasa Perbandingan Program Minggu Ceria 17 Oktober 2021 Radio Swara Kenanga UMPurworejo dan Rencana Pelaksanaan pembelajaran di Kelas X SMA - Nurul Fitriany; Umi Faizah; Joko Purwanto (SURYA BAHTERA, 2022)
Abstract: The purpose of this study is to describe the use of the language style of the Ceria Sunday program, October 17 2021 andthe implementation plan of learning in ten class Senior Haig School. The data and sources of this research are the recording of the Minggu Ceria program October 17, 2021 Radio Swara Kenanga UMPurworejo. The object and focus of this research is comparative language style. Collecting data using observation, interview, and documentation techniques, accompanied by steps using basic tapping techniques followed by conversational engagement, recording techniques, and note-taking techniques. The research instrument is the author himself who is assisted by a data recording card. Data analysis used the agih method. The technique of presenting the results of data analysis used informal techniques. The results of this study can be concluded that (1) there is a use of comparative language styles in the Ceria Sunday program October 17 2021 at Radio Swara Kenanga UMPurworejo namely personification, allegory, antithesis, periphrasis, correction and epanorthosis, pleonasm or tautology, and prolepsis (2) implementation plan Radio program fairy tale learning is carried out using the group investigation method, basic competencies using KD 3.8 Comparing the values and language of saga and short stories. The assessment instrument consists of aspects of attitude, knowledge, and skills. Keywords: comparative language style, radio program, lesson plan